Bioactive compounds and antioxidant capacity of Chuquiraga jussieui J.F.Gmel from the highlands of Ecuador. Issue 18 (16th September 2020) - Guerrero Bonilla, Daniel A.; Granda-Albuja, María G.; Guevara, Mabel; Iturralde, Gabriel A.; Jaramillo-Vivanco, Tatiana; Giampieri, Francesca; Alvarez-Suarez, José M.
Abstract: Chuquiraga jussieui J.F.Gmel is grown between 3000 and 5000 meters above sea level throughout the Andean region of Ecuador and used by the indigenous populations of the Andes for medicinal purposes. Here, we determined the total phenolic, flavonoids, vitamin C and carotenoids content of the leaves and flowers of Ch. jussieui J.F.Gmel from different highlands of Ecuador as well as the capacity of a crude methanolic extract from the both parts of the plant to scavenge free radicals and protect red blood cell membranes from lipid oxidation. The leaves showed a high bioactive compound content in comparison to the flowers. The crude extract from the leaves proved to be more effective than the flowers in reducing iron and scavenging the DPPH, O2 − and H2 O2 radicals, as well as in protecting cellular membrane against lipid oxidation, demonstrating that Ch. jussieui J.F.Gmel represents an important source of bioactive compounds with relevant healthy properties. Graphical Abstract: